2022
DOI: 10.3389/fcvm.2022.859793
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Vitamin D Deficiency: A Link Beyond the Appearances

Abstract: Vitamin D is a steroid hormone that plays a key role in the regulation of body homeostasis, including cardiovascular function. Although the chronic deficiency of vitamin D is associated with cardiovascular risk factors, as well as with an adverse prognosis, randomized controlled trials have failed in demonstrating that dietary vitamin D supplementation could ameliorate the prognosis of patients with cardiovascular diseases, and suggested that vitamin D deficiency is the expression of the effects of other deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 174 publications
1
4
0
Order By: Relevance
“…32 Vitamin D deficiency/insufficiency has been associated with metabolic abnormalities like hypertension and diabetes. 33,34 In our study, the mean blood pressure in hypertensive patients receiving vitamin D supplements was decreased significantly from baseline and remained normal. These patients were also on stable anti-hypertensive treatment for two months prior to enrolment.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…32 Vitamin D deficiency/insufficiency has been associated with metabolic abnormalities like hypertension and diabetes. 33,34 In our study, the mean blood pressure in hypertensive patients receiving vitamin D supplements was decreased significantly from baseline and remained normal. These patients were also on stable anti-hypertensive treatment for two months prior to enrolment.…”
Section: Discussionsupporting
confidence: 45%
“…There is an association between vitamin D levels and glycemic control, which has been reported in studies suggesting that poor vitamin D status is a potential risk modifier for both types of diabetes. 34,[36][37][38] We assessed the effect on QoL of patients after vitamin D supplementation using the SF-20 questionnaire where we observed improvement in four QoL domains, namely, physical functioning, role functioning, body pain, and health perception. This modest effect may be due to the relatively short duration of exposure to vitamin D or may be due to other confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have demonstrated a link between IR and vitamin D deficiency. [12] Dyslipidemia (abnormal lipid profile levels) is a health issue worldwide in adults, especially in those with unhealthy lifestyles, obesity, and postmenopausal women. Individuals with dyslipidemia are at high risk of developing hypertension, atherosclerosis, and cardiovascular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Low-grade inflammation is an important factor involved in the pathogenesis of insulin resistance [82] and chronic Vit-D deficiency parallels with the clinical manifestations of this condition [83]. Six-month Vit-D supplementation in obese adolescents with variable baseline Vit-D status [84] and 12-week RT in obese middle-aged men with uncontrolled Vit-D status [85] significantly reduced HOMA-IR index, i.e., improved insulin resistance.…”
Section: Discussionmentioning
confidence: 99%